Optimization of ventilation system in deep well gold mine based on Ventsim - Sun Yuhao; Wang Jie (E3S Web of Conferences)
To address issues like excessive energy consumption, insufficient deep air intake, and improper airflow control, optimizations were made to both the shallow and deep ventilation systems. By conducting comprehensive wind measurements across the entire mine, the distribution of underground wind speed and airflow was thoroughly understood, allowing for an analysis of the mine’s ventilation capacity and wind resistance. A theoretical model of underground ventilation and wind resistance was developed using Ventsim software. Additionally, a three-dimensional numerical model of Linglong Gold Mine’s ventilation system was created with three-dimensional ventilation numerical simulation software. This model facilitated dynamic airflow simulation within the ventilation system, enabling the proposal of optimization and adjustment plans. The effects of air regulation were simulated and analyzed to optimize the ventilation network. Results indicate that, following the optimal adjustment scheme for deep airflow distribution, airflow disorder can be resolved and air supply in deep mining areas can be increased, effectively addressing the issue of insufficient air supply there. Post-optimization, the ventilation system’s stability is improved, and air volume distribution becomes more reasonable, providing valuable guidance for Linglong Gold Mine’s ventilation management.